Sistema elevatório de água movido à energia eólica para o abastecimento de comunidades ribeirinhas do Baixo Tocantins - CABRAL, Claudio Lucio Moreira (2018)
Currently the world is growing in terms of industrial production in order to meet the increasing demand dynamics of a population increasingly consumerist. Walking parallel to this growth are research related clean energy sources. Among these sources is wind, which in recent years has gained attention for its potential especially noticeable in coastal regions. This paper presents basic concepts about wind energy, and its history of use in Brazil and worldwide. Are also presented basic concepts of water supply systems and their history. It also presented a way to construct a new water supply system that has the wind as a driver. It is a system that combines a weather vane, in order to capture the mechanical energy of the wind, a simplified lift system consisting of a pump-to-string. Shown are important aspects ranging from design to prototype construction subjected to empirical tests that followed in its construction criteria, mainly because almost all the materials used are made of scrap. Presents the results of tests performed in the field, demonstrating the feasibility of installing the project. Implicitly, the paper also addresses issues like the need for use of clean energy sources, as is the case of the wind, because it is a very important topic considering the behavioral rhythm of society, increasingly consumerist.